Efficacy of various adjuvant chemotherapy methods in preventing liver metastasis from potentially curative colorectal cancer: A systematic review network meta‐analysis of randomized clinical trials - Xianwei Liu; Qisheng Liu; Xiaoyu Wu; Wenbing Yu; Xinmin Bao (Cancer Medicine)
Abstract Purpose Various chemotherapy administration methods have been used to prevent liver metastasis (LM) in patients with colorectal cancer (CRC). This network meta‐analysis evaluated the efficacy of these different methods in preventing LM in CRC patients who underwent curative surgery. Method A systematic search of randomized controlled trials reporting the efficacy of various adjuvant chemotherapy methods in patients with colorectal cancer who underwent curative surgery was conducted. The primary outcome was the LM rate. Results This network meta‐analysis included 19 studies reporting on 12,588 participants, comparing portal vein infusion chemotherapy (PVIC) versus hepatic arterial infusion chemotherapy (HAIC) versus systematic chemotherapy (SC) versus surgery alone. The HAIC group had the lowest LM rate when compared to the other three groups (odds ratio [OR] of PVIC vs. HAIC: 1.86; OR of SC vs. HAIC: 1.98; and HAIC vs. surgery alone: 0.43). The LM rate did not differ significantly between PVIC, SC, and surgery alone. The recurrence rates were lower for PVIC and HAIC than for surgery alone (the ORs for PVIC and HAIC were 0.73 [95% CI: 0.58–0.92] and 0.45 [95% CI: 0.26–0.77]). The mortality rates of patients undergoing PVIC and HAIC were lower than that of patients undergoing surgery alone (the ORs for PVIC and HAIC were 0.77 [95% CI: 0.64–0.93] and 0.49 [95% CI: 0.24–0.98]). Anastomotic leakage, cardiopulmonary leakage, diarrhea, nausea and vomiting, oral ulceration, wound infection, or ileus did not differ significantly between the four groups. PVIC showed the highest hepatic toxicity rate compared to those for SC, HAIC, and surgery alone. Conclusion HAIC might be a satisfactory method for preventing LM in patients with CRC undergoing curative surgery.